Building Competitive Advantage Through Halal Assurance System and Employee Performance - Fauzi, Muchammad; Mujaddid, Ade Yusuf (Journal of Digital Marketing and Halal Industry, 2022)
By general destination from research this u for test and find out by real about influence implementation of HAS on employee performance and excellence Compete in Industrial Fast food in Central Java .Study  this useful approach quantitative  with the number of samples is 101 respondents. With purposive sampling technique, analyzed use   descriptive and inferential  with analysis technique with using Structural Equation Modeling (SEM) which is operated through the AMOS program. The results of this study are existence influence real that SJH will could explain happening enhancement performance employees. Show existence influence real that performance employee will could explain happening enhancement superiority compete. Show no existence influence real that SJH will could explain happening enhancement superiority compete. Sshow that in the industry food fast Halal certified fast food. Implementation of HAS in the production process capable create employees who produce high performance and performance employee proven take effect positive significant to superiority compete. That is, performance employee will also cause happening superiority compete.